How Preservice Teachers Perceive Their Collaboration Team Working Skills During PjBL - Maulidah, Rifa’atul; Susanti, Ernita; Mahmudah, Ifa Rifatul; Makiyah, Yanti Sofi (Jurnal Penelitian Pendidikan IPA, 2023)
The PjBL approach is applied to the Physics Laboratory Management course to support the achievement of learning outcomes. Through PjBL, preservice teachers are given assignments related to their future work as teachers and are required to complete them in groups. This study aims to determine how preservice teachers perceive their collaborative skills while interacting with group members when completing assignments. This research applied a mixed-methods approach to better understand research problems by quantitative and qualitative data. We employ total population sampling to examine the entire population with a particular set of characteristics from 67 people who completed the group project assignment. We analyze and describe the quantitative and qualitative data results to answer preservice teachers' perceptions of their collaborative team working skills during PjBL. We prefer the explanatory design method, where qualitative data is needed to explain the significant quantitative results. As a result, Preservice Teachers' perception shows that during PjBL, they have obtained collaboration skills in teamwork, managing conflicts, decision making, and communication skills. From the interviews, we dig up additional information about their complaints about the difficulty of completing projects and working in teams. However, the benefits of the additional skills they get are more profitable than their challenges. This analysis informs us that Preservice Teachers show a more significant positive response regarding collaboration skills during PjBL. It can be considered to continue to bring up collaboration skills in any given learning approach.